The Effect of the Addition of Chokeberry Fiber on the Quality of Sheep’s Milk Fermented by Lactobacillus rhamnosus and Lactobacillus acidophilus - K. Szajnar; M. Pawlos; A. Znamirowska (International Journal of Food Science)
The global market for sheep’s milk and its products is increasing due to higher demand for cheese and traditional dairy products, and as a novelty, sheep’s milk is an ingredient in infant formulas and nutraceuticals. The aim of this study was to determine the properties of fermented sheep’s milk, which combines probiotic benefits with increased dietary fiber content. The influence of the applied dose of chokeberry fiber on the growth of living cells of Lactobacillus acidophilus and Lactobacillus rhamnosus in fermented sheep’s milk was also evaluated. Sheep milk with the addition of 0% (control sample), 1.5%, and 3.0% chokeberry fiber was fermented by two different probiotic monocultures L. acidophilus and L. rhamnosus. In the fermented milk, pH value, syneresis (%), color, and texture were determined. Furthermore, the microbiological analysis and an organoleptic evaluation were performed. With the increasing dose of chokeberry fiber, the pH value decreased already before the fermentation process. After fermentation, the milk’s pH values with fiber were still lower than those in the control sample. Presumably, more acidic metabolites were produced by L. acidophilus, causing a more intense reduction of the pH value than L. rhamnosus both in control milk and in milk with the addition of fiber. The addition of chokeberry fiber affected the stimulation of the growth of both types of bacteria. In the milk sample without fiber addition, a more significant number of viable cells were counted for L. acidophilus by 0.5 log CFU g-1 more than the milk fermented with L. rhamnosus. Furthermore, in milk fermented by L. acidophilus with 1.5% chokeberry fiber (LA1), the number of viable bacterial cells was higher than that in milk fermented by L. rhamnosus with the same addition of fiber (LR1). However, in sample LA3, the number of viable bacterial cells was lower than that in sample LR3. Tested fermented sheep milk met the Recommendation of the International Dairy Federation’s requirements regarding the number of live bacterial cells for dairy probiotics. The addition of chokeberry fiber increased syneresis in each fermented milk group, regardless of the bacteria used for fermentation. Moreover, the use of fiber caused a significant reduction in brightness L∗, an increase of red color, and a decrease of yellow color. Milk fermented with L. acidophilus was characterized by a harder gel, compared to their analogues fermented with L. rhamnosus. The addition of fiber intensified the sour taste and the taste of the additive in both types of fermented sheep milk.